RENDEMEN KITOSAN LIMBAH CANGKANG KERANG SIMPING (Amusium pleuronectes) DAN KERANG KEPAH (Polymesoda erosa) DARI KENDAL JAWA TENGAH - Ariyanti Ariyanti; Eni Masruriati; Arin Widya Nuari; M. Himawan Yoga Syahputra (Universitas Wahid Hasyim Semarang, 2019)
ABSTRACTChitosan is the result of the deacetylation process of chitin by removing acetyl groups to obtain polymer compounds and glucosamine. Utilization of chitosan derived from waste of Amusium pleuronectes and Polymesoda erosa has not been maximize. This study aims to determine the highest chitosan yield in Amusium pleuronectes and Polymesoda erosa. The method used in this study was a deacetylation isolation method with five replications. The yield of the yield content was analyzed by univariate and bivariate with spps 19.0 using a ttest. Based on the results of the research on the sample of Amusium pleuronectes and Polymesoda erosa, the highest yield of chitosan at 75% b/v concentration of NaOH was 6,972% b/v for Amusium pleuronectes and 5.972% b/v for Polymesoda erosa. The results showed that NaOH concentrations of 15v, 25, 50, and 75% b/v could affect the chitin change to chitosan against Amusium pleuronectes and Polymesoda erosa.Keywords: Amusium pleuronectes, Polymesoda erosa, deacetylation, chitin, chitosan